What is the impact of PCSK9 rs505151 and rs11591147 polymorphisms on serum lipids level and cardiovascular risk: a meta-analysis - Qiu, Chengfeng (Lipids Health Dis, 2017)
BACKGROUND: PCSK9 rs505151 and rs11591147 polymorphisms are identified as gain- and loss-of-function mutations, respectively. The effects of these polymorphisms on serum lipid levels and cardiovascular risk remain to be elucidated. METHODS: In this meta-analysis, we explored the association of PCSK9 rs505151 and rs11591147 polymorphisms with serum lipid levels and cardiovascular risk by calculating the standardized mean difference (SMD) and odds ratios (OR) with 95% confidence intervals (CI). RESULTS: Pooled results analyzed under a dominant genetic model indicated that the PCSK9 rs505151 G allele was related to higher levels of triglycerides (SMD: 0.14, 95% CI: 0.02 to 0.26, P = 0.021, I(2) = 0) and low-density lipoproteins cholesterol (LDL-C) (SMD: 0.17, 95% CI: 0.00 to 0.35, P = 0.046, I(2) = 75.9%) and increased cardiovascular risk (OR: 1.50, 95% CI: 1.19 to 1.89, P = 0.0006, I(2) = 48%). The rs11591147 T allele was significantly associated with lower levels of total cholesterol (TC) and LDL-C (TC, SMD: -0.45, 95% CI: -0.57 to −0.32, P = 0.000, I(2) = 0; LDL-C, SMD: -0.44, 95% CI: -0.55 to −0.33, P = 0.000, I(2) = 0) and decreased cardiovascular risk (OR: 0.77, 95% CI: 0.60 to 0.98, P = 0.031, I(2) = 59.9) in Caucasians. CONCLUSIONS: This study indicates that the variant G allele of PCSK9 rs505151 confers increased triglyceride (TG) and LDL-C levels, as well as increased cardiovascular risk. Conversely, the variant T allele of rs11591147 protects carriers from cardiovascular disease susceptibility and lower TC and LDL-C levels in Caucasians. These findings provide useful information for researchers interested in the fields of PCSK9 genetics and cardiovascular risk prediction not only for designing future studies, but also for clinical and public health applications.